Origins and organization of the NHLBI State of the Science Workshop: Generating a national blueprint for future research on factor VIII inhibitors. Issue 4 (22nd July 2019) - Sabatino, Denise E.; Pipe, Steven W.; Nugent, Diane J.; Soucie, J. Michael; Hooper, W. Craig; Hoots, W. Keith; DiMichele, Donna M.
Abstract : Introduction: The major complication of protein replacement therapy for haemophilia A is the development of anti‐FVIII antibodies or inhibitors that occur in 25%‐30% of persons with severe haemophilia A. Alternative therapeutics such as bypassing agents or immune tolerance induction protocols have additional challenges and are not always effective. Aim: Assemble a National Heart, Lung and Blood Institute (NHLBI) State of the Science (SOS) Workshop to generate a national blueprint for research on inhibitors to solve the problem of FVIII immunogenicity. Methods: An Executive Steering Committee was formed in October 2017 to establish the scientific focus and Scientific Working Groups for the SOS Workshop in May 2018. Four working groups were assembled to address scientific priorities in basic, translational and clinical research on inhibitors. Results: Working Group 1 was charged with determining the scientific priorities for clinical trials to include the integration of non‐intravenous, non‐factor therapeutics including gene therapy into the standard of care for people with haemophilia A with inhibitors. Working Group 2 established the scientific priorities for 21st‐century data science and biospecimen collection for observational inhibitor cohort studies. The scientific priorities for acquiring an actionable understanding of FVIII immunogenicity and the immunology of the host response and FVIII tolerance were developed by Working Group 3. Working Group 4 designed prospective pregnancy/birth cohorts to study FVIII immunogenicity, inhibitor development and eradication. Conclusion: The NHLBI SOS Workshop generated a focused summary of scientific priorities and implementation strategies to overcome the challenges of eradicating and preventing inhibitors in haemophilia A.